Neuropsychological effects of the CSMD1 genome‐wide associated schizophrenia risk variant rs10503253. (22nd February 2013) - Donohoe, G.; Walters, J.; Hargreaves, A.; Rose, E.J.; Morris, D.W.; Fahey, C.; Bellini, S.; Cummins, E.; Giegling, I.; Hartmann, A.M.; Möller, H.‐J.; Muglia, P.; et al.
Abstract : The single‐nucleotide polymorphism (SNP) rs10503253, located within the CUB and Sushi multiple domains‐1 ( CSMD1 ) gene on 8p23.2, was recently identified as genome‐wide significant for schizophrenia (SZ), but is of unknown function. We investigated the neurocognitive effects of this CSMD1 variant in vivo in patients and healthy participants using behavioral and imaging measures of brain structure and function. We compared carriers and non‐carriers of the risk 'A' allele on measures of neuropsychological performance typically impaired in SZ (general cognitive ability, episodic and working memory and attentional control) in independent samples of Irish patients ( n  = 387) and controls ( n  = 171) and German patients (205) and controls ( n  = 533). Across these groups, the risk 'A' allele at CSMD1 was associated with deleterious effects across a number of neurocognitive phenotypes. Specifically, the risk allele was associated with poorer performance on neuropsychological measures of general cognitive ability and memory function but not attentional control. These effects, while significant, were subtle, and varied between samples. Consistent with previous evidence suggesting that CSMD1 may be involved in brain mechanisms related to memory and learning, these data appear to reflect the deleterious effects of the identified 'A' risk allele on neurocognitive function, possibly as part of the mechanism by which CSMD1 is associated with SZ risk. Abstract : The CSMD1 variant rs10503253, a genome‐wide supported schizophrenia risk variant, is associated with subtle deficits on a range of neuropsychological measures in patients with schizophrenia and controls.